Évaluation de la vulnérabilité des communautés de montagne face au changement climatique. Région Beni-Mellal-Khénifra, Maroc - Mounia Achbah; Abdellatif Khattabi; Diane Pruneau; Taieb Boumeaza (VertigO)
In recent years, Morocco has experienced an increase in temperatures and a decrease in precipitation, resulting in adverse effects on resource productivity, population well-being, and heightened vulnerability. This study focuses on analyzing the perceptions of the local population regarding the impacts of climate change on their livelihoods. The research was conducted in the mountainous area of the Beni Mellal-Khénifra region, Morocco, employing a participatory approach through seven workshops and twenty semi-structured interviews. In addition to qualitative methods, data were gathered from various sources, including statistics from the National Agency for Water and Forests, the Office for Development Cooperation, the High Commission for Planning, and the Department of Agriculture. The assessment of vulnerability through livelihoods and the measurement of the criticality of climate impacts (specifically droughts and floods) were integral to the research. The findings revealed that drought was perceived as the most significant hazard affecting resources, followed by floods. Utilizing a vulnerability matrix, resources were categorized into three groups based on their susceptibility to climate change: i) highly vulnerable resources (agricultural land, livestock, and arboriculture), ii) vulnerable resources (water resources, forests, and economic resources tied to cereal cultivation, beekeeping, and market gardening); and iii) moderately vulnerable resources, comprising those impacted by flooding (human lives, equipment, and material goods).